2024
DOI: 10.3389/fbuil.2023.1334005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the challenges influencing the adoption of smart building technologies

Saleh Baharetha,
Ashraf M. Soliman,
Mohammad A. Hassanain
et al.

Abstract: Introduction: Over the past few decades, there has been an increasing focus on Smart Building Projects (SBP) and the technologies associated with them. Numerous studies have been conducted globally to define smart building technologies (SBT), identify challenges, and explore areas for improvement. This study aims to examine the concept and terminology of SBT and the expertise and experience of participants in SBP in the Arab Gulf countries, specifically Saudi Arabia. The study also investigates the challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Project development requires a detailed understanding of stakeholders' needs. In this sense, Baharetha et al [68] highlight that distinguishing the intelligence requirements of owners, users, operators, and facility managers is complex. Furthermore, the characteristics and specificities of smart buildings and the increase in design changes [28] require using technologies such as BIM to develop the design process, which is not always accessible to small and medium-sized construction companies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Project development requires a detailed understanding of stakeholders' needs. In this sense, Baharetha et al [68] highlight that distinguishing the intelligence requirements of owners, users, operators, and facility managers is complex. Furthermore, the characteristics and specificities of smart buildings and the increase in design changes [28] require using technologies such as BIM to develop the design process, which is not always accessible to small and medium-sized construction companies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding "more complex design and construction", authors such as Rodrigues et al [28], Yang et al [54], Gobbo Jr. et al [33], and Balta-Ozkan et al [63] found that smart buildings, compared to traditional buildings, imply more complex design and construction procedures. These are factors that increase complexity, the need for more changes in the design [28,44,61], the incorporation of a large number of systems in the building [31], the need for systems optimization [36], the lack of understanding of the needs of smart building users [33,56,68], and the need to satisfy specific requirements of both the users and owners of these buildings [28,30,31,57]. Furthermore, the design of privacy solutions for IoT [60] and the absence of a common framework that efficiently integrates IoT aspects with operational-level construction practices increases complexity [39,49]; Apanavičien ė and Shahrabani [13] highlight that the need for scalable and cost-effective solutions adds a challenging component to the overall complexity faced in creating smart buildings.…”
Section: The Barriers Limiting the Development Of Smart Buildingsmentioning
confidence: 99%